GABA and l-theanine mixture decreases sleep latency and improves NREM sleep - Suhyeon Kim; Kyungae Jo; Ki-Bae Hong; Sung Hee Han; Hyung Joo Suh (Taylor & Francis Group, 2019)
Context: γ-Aminobutyric acid (GABA) is the main inhibitory neurotransmitter and it is well established that activation of GABAA receptors favours sleep. l-Theanine, a naturally occurring amino acid first discovered in green tea, is a well-known anti-anxiety supplement with proven relaxation benefits. Objective: This study investigated the potential synergistic sleep enhancement effect of GABA/l-theanine mixture. Materials and methods: Pentobarbital-induced sleep test was applied to find proper concentration for sleep-promoting effect in ICR mice. Electroencephalogram (EEG) analysis was performed to investigate total sleeping time and sleep quality in normal SD rats and caffeine-induced awareness model. Real-time polymerase chain reaction (RT-PCR) was applied to investigate whether the sleep-promoting mechanism of GABA/l-theanine mixture involved transcriptional processes. Results: GABA/l-theanine mixture (100/20 mg/kg) showed a decrease in sleep latency (20.7 and 14.9%) and an increase in sleep duration (87.3 and 26.8%) compared to GABA or theanine alone. GABA/l-theanine mixture led to a significant increase in rapid eye movement (REM) (99.6%) and non-REM (NREM) (20.6%) compared to controls. The use of GABA/l-theanine mixture rather than GABA or l-theanine alone restored to normal levels sleep time and quality in the arousal animal model. The administration of GABA/l-theanine led to increased expression of GABA and the glutamate GluN1 receptor subunit. Conclusions: GABA/l-theanine mixture has a positive synergistic effect on sleep quality and duration as compared to the GABA or l-theanine alone. The increase in GABA receptor and GluN1 expression is attributed to the potential neuromodulatory properties of GABA/l-theanine combination, which seems to affect sleep behaviour.